2016
DOI: 10.1210/jc.2015-3108
|View full text |Cite
|
Sign up to set email alerts
|

Central Diabetes Insipidus in Infancy With or Without Hypothalamic Adipsic Hypernatremia Syndrome: Early Identification and Outcome

Abstract: Neonatal CDI may be transient or permanent. These vulnerable patients have high rates of comorbidity and require careful monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…Существуют ограниченные исследования, связанные с лечением неонатального центрального несахарного диабета деспопрессином, но в целом этот препарат рекомендуется применять с осторожностью из-за высокой вероятности сильных скачков уровня сывороточного натрия [8]. Для коррекции повышенного уровня натрия в крови и гипертермии была рассчитана суточная потребность ребенка в жидкости.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Существуют ограниченные исследования, связанные с лечением неонатального центрального несахарного диабета деспопрессином, но в целом этот препарат рекомендуется применять с осторожностью из-за высокой вероятности сильных скачков уровня сывороточного натрия [8]. Для коррекции повышенного уровня натрия в крови и гипертермии была рассчитана суточная потребность ребенка в жидкости.…”
Section: Discussionunclassified
“…There were limited resources to do the antidiuretic hormone level and genetic mutation but the history of natal and postnatal course of the baby was suggestive of central diabetes insipidus. There are limited studies related the treatment of neonatal central DI by desmopressin but generally it is not recommended as initial management but the last choice as there is high probability of wide swings in serum sodium (8) The fluid requirement per 24 hours was calculated and it was given to the baby as bottle milk feeds and plain water which successfully controlled the hypernatremia.…”
Section: Discussionmentioning
confidence: 99%
“…More clarity in managing hydrocephalus associated with aHPE is always a goal, and this case leads us to investigate the effects of shunting on the hypothalamic osmoreceptor function, which may contribute to adipsic central diabetes insipidus [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Although MRI finding of an absent posterior pituitary hyperintense signal is not diagnostic, it is awell-known characteristic of CDI[11][12][13] . Ectopic posterior pituitary was observed in three neonates in a study reported by Djermane et al8) . An ectopic posterior pituitary may be the cause of CDI due to a structural anomaly in the current patient.…”
mentioning
confidence: 81%
“…Idiopathic CDI is thought to account for 12% to 24% of cases 2) . Previous reports of CDI in preterm infants [2][3][4][5][6][7][8][9] , excluding traumatic or ischemic brain injuries, are summarized in Table 1.…”
Section: Case Reportmentioning
confidence: 99%